GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGELOLAAN KESISWAAN DI SMA NEGERI 1 NGAGLIK KABUPATEN SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The purpose of this research is intended to describe the leadership style of the principal in managing the high school students at Public Senior High School 1 Ngaglik in Sleman regency. The research focus on general leadership by the principal, the principal's leadership style associated with the management of student affairs at Public Senior High School 1 Ngaglik. This study used a qualitative approach, data sources or informants include: principals, vice-principals, coaches OSIS, teachers, staff and students and also documents relating to the implementation of student programs. Data collection techniques are observation, interviews and document scrutiny.The results of this study describe that principal leadership in his capacity as the person in charge of education in Public Senior High School 1 Ngaglik tends to delegate more responsibility to the assistant principal and coordinator of his staff, but in the field of student affairs, in addition to the principal appoint the vice-principal and the staff for student council , the role of the principal is still quite high. In managing the students, the principal has strong leadership style and firm as well as its policy on student activities programs decide by himself more likely the marching drills program of Sleman District Military Command and the determination of class divisions. The school principal alsohas a little pushy character and often provide punishment in carrying out the students. The principal tries to use the capacity of Public Senior High School 1 Ngaglik and try to overcome the inhibiting factors in managing studenst. By applying the style, headmasters of the school has restoredorderly conditions successfully and the poor performance has been changed to be orderly schools with discipline students and began to show their achievements both in academic and non-academic. So that the vision, mission: discipline, quality and pride which is proclaimed by the principal is getting closer to reality.